Overexpression of CD36 and Acyl-CoA Synthetases FATP2, FATP4 and ACSL1 Increases Fatty Acid Uptake in Human Hepatoma Cells - Krammer, Julia (Ivyspring International Publisher, 2011)
Background: Understanding the mechanisms of long chain fatty acid (LCFA) uptake in hepatic cells is of high medical importance to treat and to prevent fatty liver disease (FLD). ACSs (Acyl-CoA synthetases) are a family of enzymes that catalyze the esterification of fatty acids (FA) with CoA. Recent studies suggest that ACS enzymes drive the uptake of LCFA indirectly by their enzymatic activity and could promote special metabolic pathways dependent on their localization. The only protein located at the plasma membrane which has consistently been shown to enhance FA uptake is CD36. Aims: The current study investigated whether ACSs and CD36 could regulate hepatic LCFA uptake. Methods and Results: FATP2 and FATP4 were both localized to the ER of HuH7 and HepG2 cells as shown by double immunofluorescence in comparison to marker proteins. ACSL1 was located at mitochondria in both cell lines. Overexpression of FATP2, FATP4 and ACSL1 highly increased ACS activity as well as the uptake of [3H]-oleic acid and fluorescent Bodipy-C12 (B12) fatty acid. Quantitative FACS analysis showed a correlation between ACS expression levels and B12 uptake. FATP2 had the highest effect on B12 uptake of all proteins tested. CD36 was mainly localized at the plasma membrane. Whereas [3H]-oleic acid uptake was increased after overexpression, CD36 had no effect on B12 uptake. Conclusion: Uptake of LCFA into hepatoma cells can be regulated by the expression levels of intracellular enzymes. We propose that ACS enzymes drive FA uptake indirectly by esterification. Therefore these molecules are potential targets for treatment of nonalcoholic fatty liver disease (NAFLD) or steatohepatitis (NASH).